Sprouting of oats: A new approach to quantify compositional changes. Issue 6 (20th August 2019) - Krapf, Julia; Kandzia, Franziska; Brühan, Juliane; Walther, Goeran; Flöter, Eckhard
Abstract: Background and objectives: The aim of this research was to gain a deeper insight into the effect caused by the addition of sprouted oat to food products. The effect of temperature and duration of the sprouting process was systematically studied by sprouting oat grains between 10 and 30°C for up to 3 days. Findings: Overall, it was found that temperatures between 20 and 25°C yield the most dramatic changes in the properties of sprouted oats. Based on the data, a simple system to characterize the sprouting progress by a visual inspection of the lengths of the coleoptile and radicles was developed. This degree of sprouting (DoS) was correlated with further grain properties. Conclusions: It was found that an exponential relationship between the DoS and grain properties existed. Furthermore, the observed increase in the reducing sugar content (up to 14.6 g/100 g) with increasing DoS was closely related to the increase in α‐amylase activity (up to 25 U/g). Significance and novelty: The good predictive power found indicates that the application of the concept degree of sprouting could develop into a reliable characterization method for sprouted grains usable for product development and specification.